Management and Outcome of Severe Sepsis and Septic Shock Patients - Lamichhane, Sabitri; Manandhar, Nayan; Dhakal, Shailendra; Shakya, Yagya Laxmi (Journal of Nepal Health Research Council, 2018)
Background: Severe sepsis and septic shock are major causes of morbidity and mortality worldwide and need immediate medical attention. Early recognition, fluid resuscitation and early antimicrobials are the mainstays of sepsis therapy. This study analyzed the management strategies of severe sepsis and septic shock and evaluated its impact. Methods: A prospective study was conducted on patients admitted through emergency department of Tribhuvan University Teaching Hospital of Nepal, who were diagnosed with severe sepsis and septic shock. Results: A total of 85 patients were diagnosed as severe sepsis and septic shock with 45 female patients and mean age 47.69 years ranging from 18 to 83 years. Pneumonia (45.9%) was found to be the major source of infection. The most commonly prescribed antibiotics and vassopressor at emergency department were ceftriaxone (24.7%) and norepinephrine (44.7%) respectively. The mean length of stay in Emergency department was 13.01 ± 7.03 h, while it was 11.27 ± 5.26 days in hospital. A total of 31 (36.5%) septic patients died. Deceased patients were found to have greater age, higher Acute Physiology and Chronic Health Evaluation II (APACHE II) score and presence of co-morbid conditions. Conclusions: This study looked in-depth on management and outcome of patients with severe sepsis and septic shock. Mortality from severe sepsis and septic shock were high, but similar to other studies. Keywords: Antimicrobial therapy; emergency department; mortality; septic shock; severe sepsis.